Strategi Guru Pendidikan Agama Islam Dalam Mengembangkan Nilai-Nilai Toleransi Peserta Didik - Chanif, Mohamad Hanif; Syamsuddin, Ahmad Muzaky (Pendidikan Islam Pascasarjana IAIN Jember, 2025)
The purpose of this study is to provide an overview of teacher strategies in instilling values oftolerance in students with the aim of preventing intolerant attitudes and radicalism and explainingmethods of tolerance education. Looking at the conflict of religious polarization that has occurredin Indonesia recently, especially regarding matters related to differences in understanding andbeliefs. These differences cause conflicts based on a lack of attitudes and characteristics oftolerance. This study uses a field research method with a qualitative approach. The results of thestudy develop the values of religious tolerance is very important for realizing a safe, peaceful, andprosperous order of life. Religious tolerance education if implemented from an early age, it willform a character that prioritizes an attitude of tolerance or tolerance. Meanwhile, the method ofreligious tolerance education can be done through the method of role models, advice andhabituation.Keyword: Strategy, developing tolerance values